Pemodelan Jumlah Kasus Penderita Demam Berdarah Dengue (DBD) menggunakan Metode Integer Valued Autoregressive Moving Average (INARMA) - Inayah, Nurul; Kasse, Irwan; Sauddin, Adnan (Universitas Islam Negeri Alauddin Makassar, 2024)
The Integer Valued Autoregressive Moving Average (INARMA) method is used to analyze data with count type or integer type and Poisson distribution. Based on this, the data to be analyzed in this study is the total data, namely the data on the number of cases of patients with DHF (Dengue Hemorrhagic Fever), which is a disease that is transmitted through the bite of the Aedes aegypti mosquito. The high number of dengue fever in Indonesia, especially in the Sidoarjo area which tends to fluctuate every month, is made a prediction model as a step to determine the prediction of the number of dengue patients in the future. The model obtained after conducting the time series analysis process is INARMA(1,0,0) or INAR(1).